Aerobic exercise alleviates pyroptosis-related diseases by regulating NLRP3 inflammasome - Hu, Shujuan; Wan, Xingxia; Li, Xianhui; Wang, Xianwang (Frontiers in Physiology, 2022)
Pyroptosis plays a crucial role in a variety of human diseases, including atherosclerosis, obesity, diabetes, depression, and Alzheimer’s disease, which usually release pyroptosis-related cytokines due to inflammation. Many studies have demonstrated that aerobic exercise is a good option for decreasing the release of pyroptosis-related cytokines. However, the molecular mechanisms of aerobic exercise on pyroptosis-related diseases remain unknown. In this review, the effects of aerobic exercise on pyroptosis in endothelial cells, adipocytes and hippocampal cells, and their potential mechanisms are summarized. In endothelial cells, aerobic exercise could inhibit NOD-like receptor protein 3 (NLRP3) inflammasome-mediated pyroptosis by improving the endothelial function, while reducing vascular inflammation and oxidative stress. In adipocytes, aerobic exercise has been shown to inhibit pyroptosis by ameliorating inflammation and insulin resistance. Moreover, aerobic exercise could restrict pyroptosis by attenuating microglial activation, neuroinflammation, and amyloid-beta deposition in hippocampal cells. In summary, aerobic exercise alleviates the pyroptosis-related diseases by regulating the NLRP3 inflammation signaling.